Protagonistas! a força das mulheres da periferia na pastoral da mulher, Região Episcopal Brasilândia - Aleixo, Ornela Maria (2017)
This work, Protagonists! The strength of women from the periphery in the pastoral care of women, the Brasilia episcopal region, is the result of contact with women from the outskirts of São Paulo, in the northwestern area, who meet monthly in a women's group called the Pastoral Care of Women in the Brasilia Episcopal Region. Our aim is to understand how those women became protagonist of their lives despite the unfavorable context of the place where they live, characterized by deep material and social deprivations. We focused on a particularity of that neighborhood which helped them to approach to their reality differently from how they would usually do in such social conditions, the existence there of the CEBs and the group Women Pastoral in the newborn Brasilândia Episcopal region, funded in 1989. Those ecclesial movements with social and political engagement fundamentally influenced those women’s live paths, however they were not responsible by the flourishment of the social subject and protagonism in each of them. We found out their stories through interviews guided by a questionnaire. After the transcription of the interviews, we analyzed those women life experiences making use of Max Weber’s comprehensive sociology and of Alain Touraine’s analysis in order to understand how protagonism happened in their lives. Then we established two analyses categories, the individual and the social subject. Studying the protagonism of women from outskirts involved in ecclesial movements engaged with social and political actions, we want to make them visible to society once they are usually unseen. Many see them as plain individuals, those who adopts the stereotyped view that defines the geographical place where they live. These women came from and are in outskirts, they broke the cycle of violence and abandonment, the isolation from the other women around them, showing that they are simply strong women